Legal protection of human rights of prisoners in Vietnam - Nguyen, Thi Thanh Tram (Đại học Quốc gia Hà Nội, 2020)
Human rights are a growing concern in Vietnam, especially after the adoption of the Constitution of 2013. This Constitution is a basis for promulgating and completing the legal provisions on human rights in the enforcement of criminal rulings. Due to confinement, prisoners’ human rights are controlled and limited in certain degrees. As a result, prisoners’ human rights are easily violated. The consequences of those violations are serious when it comes to fundamental rights such as the right to live, the right to be ensured a proper living standard, as well as political rights. In order to protect prisoners’ human rights, many Governments have proposed and enacted many provisions based on international standards and their domestic backgrounds. Ensuring human rights includes various methods and measures. One of the most important measures is institutionalization by legal regulations on the basis of international legal criteria. Through studying the laws of some countries and international standards, this paper argues that Vietnamese laws have been compatible with international legal norms, especially the special human rights of prisoners. However, there remains several shortcomings and limitations in the laws. After observing the measures to ensure human rights from other countries, this paper also draws some lessons, from which some solutions are suggested to better protect human rights of prisoners in Vietnam.